A high temperature resistant zirconium oxide ceramic material and its processing technology

By adding yttrium oxide, silicon carbide, calcium oxide and modified silicon carbide to high-temperature zirconia ceramic materials, and combining metal titanium and alumina, the problems of stability and thermal shock resistance of ceramic materials at high temperatures are solved, and the problem of ceramic materials is achieved. Highly efficient mechanical properties and high-temperature antioxidant effect.

CN118145992BActive Publication Date: 2024-12-17WUHAN KONUS NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410260309.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2024-12-17
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

High temperature-resistant ceramic materials are prone to cracks, peeling or collapse when the temperature changes rapidly. The existing technology is difficult to effectively solve the stability problem of tetragonal crystal phase t-ZrO2 at room temperature, and cracks are caused by glass phases on the interface between silicon carbide and zirconia. Increase, affecting the strength of the material.

Method used

Using the combination of materials such as zirconia, yttrium oxide, silicon carbide and calcium oxide, and through ball milling, vacuum drying, grinding, prepressing treatment and sintering, modified silicon carbide and composite ceramic materials are formed, and metal titanium and aluminum oxide are added. To enhance mechanical properties and thermal shock resistance, and improve high-temperature oxidation resistance through aluminum doping molybdenum disilide.

Benefits of technology

The high heat resistance and excellent mechanical properties of ceramic materials at high temperatures of 1800℃-1850℃ are achieved, and the bending strength, fracture toughness and high-temperature oxidation resistance are improved, and thermal stress and oxidation strength losses are reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of high temperature resistant ceramics, specifically to a high temperature resistant zirconium oxide ceramic material and its processing technology. The present invention comprises the following process steps: mixing zirconium oxide, yttrium oxide, silicon carbide and calcium oxide by ball milling, vacuum drying, grinding and screening, pre-pressing treatment, sintering, grinding and polishing to obtain a ceramic material. The present invention uses zirconium oxide as the matrix of the ceramic material, adds silicon carbide for toughening, and improves the high temperature mechanical properties of the ceramic material; adds rare earth oxide yttrium oxide and alkali metal oxide calcium oxide to improve the stability of the system, thereby obtaining a ceramic material with high heat resistance, which can withstand high temperatures of 1800°C-1850°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high temperature resistant ceramics, in particular to a high temperature resistant zirconia ceramic material and a processing technology thereof. Background Art

[0002] Zirconia is a common oxide ceramic. Its crystal structure gives it excellent material and chemical properties, and has excellent mechanical properties. It can be used as a matrix material for refractory ceramics and ultra-high temperature structural ceramics. At different temperatures, pure zirconia has three polycrystalline phases, including cubic phase (c-ZrO2), tetragonal phase (t-ZrO2) and monoclinic phase (m-ZrO2), and the performance of different phases varies greatly. In order to keep the tetragonal phase (t-ZrO2) at room temperature, stabilizers such as yttrium oxide, magnesium oxide, calcium oxide, cerium oxide, etc. are usually added to dissolve in the lattice of zirconia, so that it forms a stable or metastable tetragonal phase. However, as a highly efficient thermal protection material, high-temperature ceramic materials often involve rapid changes in temperature during use. The yttrium-stabilized zirconia material produced will produce a large temperature gradient and thermal stress inside, resulting in cracks, peeling or collapse. Therefore, we propose a high-temperature resistant zirconia ceramic material and its processing technology. Summary of the invention

[0003] The object of the present invention is to provide a high temperature resistant zirconia ceramic material and a processing technology thereof to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a processing technology of high temperature resistant zirconia ceramic material, comprising the following process steps:

[0005] Zirconium oxide, yttrium oxide, silicon carbide and calcium oxide are ball-milled and mixed, vacuum-dried, ground and sieved, pre-pressed, sintered, ground and polished to obtain a ceramic material.

[0006] Furthermore, the process conditions of ball milling mixing are: ball milling speed 250-480 r / min, ball milling time 2-24 h.

[0007] Furthermore, the process conditions of vacuum drying are: process temperature 60-80° C., and drying time 8-12 h.

[0008] Furthermore, the process conditions for grinding and screening are: grinding through a 170-250 mesh sieve.

[0009] Furthermore, the process conditions of the pre-pressing treatment are: cold isostatic pressing, pressure 150-200 MPa, time 120-200 s.

[0010] Furthermore, the sintering is performed by hot pressing sintering or microwave sintering;

[0011] The process conditions of hot pressing sintering are: in argon atmosphere, sintering temperature 1250-1350℃, holding time 2h, sintering pressure 30MPa;

[0012] The process conditions of microwave sintering are: argon atmosphere, sintering temperature 1300-1400°C, and insulation time 2h.

[0013] Further, the ceramic material comprises the following mass components: 2.0-5.3% yttrium oxide (Y2O3), 3-6% silicon carbide (SiC) and 0.5-1.0% calcium oxide (CaO), and the balance is zirconium oxide (ZrO2);

[0014] Zirconia: particle size 100-500nm, sourced from Jiaozuo Lifeng Industrial Co., Ltd.

[0015] Yttrium oxide: 5μm, from Jiangyin Jiahua New Materials Resources Co., Ltd.;

[0016] Silicon carbide: 45μm, from Huayu Abrasives Factory, Zhengzhou High-tech Industrial Development Zone;

[0017] Calcium oxide: Sourced from Chengdu Kelon Chemical Reagent Factory.

[0018] In the above technical scheme, zirconium oxide (ZrO2) is a stable compound of zirconium and oxygen, with high melting point, high hardness, low friction coefficient and good chemical inertness, and can be used to prepare high temperature resistant materials as the matrix material of high temperature resistant ceramics. It presents a surface liquid phase in a high temperature environment, dissolves a large amount of oxygen between the oxide layers, and prevents further oxidation of the prepared ceramic material. Yttria is dispersed in zirconium oxide in the form of fine crystals, which can make the high temperature stable t-ZrO2 phase exist in a stable or metastable state at room temperature, effectively improve the plasticity of the prepared ceramic material, make it have good bending strength, and show better thermal physical properties, oxygen resistance and mechanical properties. However, under long-term high temperature operation, the yttrium ions in the high temperature metastable tetragonal phase (t' phase) of yttria-stabilized zirconium oxide will be precipitated and decomposed, and martensitic phase transformation is easily produced when the temperature is lowered and cooled, accompanied by volume expansion, which reduces the high temperature thermal shock resistance of the ceramic material and affects its performance.

[0019] As a compound with strong covalent bonds, silicon carbide has the characteristics of high hardness, wear resistance, small thermal expansion coefficient, and good chemical stability at high temperatures. When added to the zirconia ceramic system as a second phase, it can toughen the ceramic material, improve its high-temperature mechanical properties, and improve the thermal shock resistance of the ceramic material. However, there is a layer of glass phase between the interface of silicon carbide and zirconia, which will cause the crack size to increase. In addition, the high residual stress in the material will form spontaneous cracks, which will have a negative impact on the strength of the ceramic material. Silicon carbide is difficult to sinter densely at high temperatures; at high temperatures and low oxygen partial pressures, active oxidation will occur, affecting its application.

[0020] The presence of alkali metal oxide calcium oxide can also serve as a stabilizer for zirconium oxide, stabilizing t-ZrO2 over a wide temperature range and improving the oxidation resistance of silicon carbide to a certain extent.

[0021] Further, the silicon carbide is prepared and modified by the following process:

[0022] Molybdenum disulfide, silicon, aluminum and activated carbon are mixed, anhydrous ethanol is added to grind, dried, and passed through a 300-400 mesh sieve; a pre-pressing treatment is continuously performed at a pressure of 190-200 MPa for 5-8 minutes; under an argon atmosphere, the gas flow rate is 400 mL / min, the temperature is increased to 630-700°C at a heating rate of 10-20°C / min, the temperature is increased to 1500-1550°C at a heating rate of 5°C / min, and the temperature is kept and sintered for 100-150 minutes; the temperature is cooled to room temperature, and the particles are crushed to less than 10 μm to obtain modified silicon carbide.

[0023] Further, the molar ratio of molybdenum disulfide, silicon, aluminum and carbon is 1:(4.25-6.0):(0.04-0.06):(0.25-2.0);

[0024] Molybdenum disulfide: purity 99.9%, particle size 10μm, sourced from Bohuasi Nanotechnology Co., Ltd.

[0025] Silicon: purity 99.5%, particle size 45μm, sourced from Beijing Dadi Zelin Silicon Industry Co., Ltd.

[0026] Aluminum: purity 99.5%, particle size 3-5μm, sourced from Angang Industrial Fine Aluminum Powder Co., Ltd.;

[0027] Activated carbon: purity 99%, particle size 50 mesh, sourced from Sinopharm Chemical Reagent Co., Ltd.

[0028] Furthermore, zirconia balls are used for grinding, the mass ratio of balls, materials and solvent is 3:1:(0.4-1.0), and the grinding time is 2-4h;

[0029] The drying process is: vacuum drying at 70-80°C for 8-12 hours.

[0030] In the above technical scheme, during the temperature-raising sintering stage, the elements aluminum and silicon first react with molybdenum disulfide to reduce molybdenum disulfide to aluminum-doped molybdenum disilicide. The aluminum element dissolves in the molybdenum disilicide to cause lattice distortion, which can effectively enhance the lattice vibration absorption. At this time, the activated carbon does not participate in the reaction. As the temperature rises, the activated carbon begins to react with silicon to generate silicon carbide, which is evenly distributed on the surface and grain boundaries of the molybdenum disilicide, hindering the growth of molybdenum disilicide and facilitating the consumption of energy generated by crack expansion, refining the grains of molybdenum disilicide, and improving its performance. When the sintering temperature is reached, silicon and activated carbon react fully at a constant temperature, and the proportion of silicon carbide increases, thereby forming modified silicon carbide containing aluminum-doped molybdenum disilicide.

[0031] Molybdenum disilicide is an intermediate phase with a high silicon content in the Mo-Si binary alloy. It has a high melting point, a low thermal expansion coefficient and excellent high-temperature oxidation resistance. It has good bending resistance and impact resistance at room temperature, and metal-like soft plasticity at high temperatures. It can effectively improve the mechanical properties and high-temperature thermal shock resistance of the produced ceramic materials. In a high-temperature oxidation environment, a dense silicon oxide film will be generated on the surface of molybdenum disilicide, making it 1800°C resistant to oxidation, which can play a role in sealing and preventing oxygen diffusion, and can effectively improve the resistance of the ceramic material system to high-temperature oxidation.

[0032] The aluminum element replaces the lattice position of silicon atoms in molybdenum disilicide, reduces the SiO2 phase in the system, forms Al2O3 strengthening particles, increases the proportion of metal bonds in the system, improves the symmetry of the crystal structure, and improves the fracture energy of molybdenum disilicide grains, which helps to improve its room temperature fracture toughness and high temperature yield strength. During the thermal cycle process, the silicon oxide film formed on the surface of molybdenum disilicide undergoes a phase transformation, and its adhesion decreases. Affected by the volume effect, the film peels off, and the introduction of aluminum elements makes it preferentially form Al2O3 during the oxidation process. Below the Al2O3-SiO2 eutectic temperature (1020℃), the Al2O3 film exhibits good adhesion and can maintain the high temperature oxidation resistance of the ceramic material system; above the eutectic temperature, silicon and aluminum are oxidized and can form a mullite phase on the film surface. SiO2 that does not participate in the formation of the mullite phase dissolves in Al2O3, which can limit the crystallization of SiO2 and improve the resistance of molybdenum disilicide to high temperature oxidation environments, thereby improving the high temperature oxidation resistance of modified silicon carbide and the ceramic material produced.

[0033] Furthermore, the ceramic material is prepared by the following process:

[0034] Mix titanium, modified silicon carbide, aluminum oxide, zirconium oxide, yttrium oxide and calcium oxide, add anhydrous ethanol to grind, dry, grind through a 170-250 mesh sieve, and perform pre-pressing.

[0035] Hot pressing sintering process: in argon atmosphere, sintering temperature is 1690-1720℃, sintering pressure is 30-40MPa, and sintering time is 10-20min; in air atmosphere, cooling to 1450-1550℃, keeping heat and pressure and sintering for 6-8h; cooling to room temperature with the furnace, grinding and polishing to obtain ceramic material.

[0036] Further, the ceramic material includes the following components by mass: 87.7 to 94.5 parts of zirconium oxide (ZrO2), 3 to 6 parts of modified silicon carbide (MoSi2(Al)-SiC), 2 to 6 parts of titanium (Ti), 4.2 to 12.7 parts of aluminum oxide (Al2O3), 2.0 to 5.3 parts of yttrium oxide (Y2O3) and 0.5 to 1.0 parts of calcium oxide (CaO).

[0037] Titanium: purity 99.5%, particle size 0.5-1 μm, sourced from Fulanshi (Beijing) Nanotechnology Co., Ltd.;

[0038] Alumina: purity 99.0%, particle size 0.5-1 μm, sourced from Aluminum Corporation of China;

[0039] Furthermore, zirconia balls are used for grinding, the mass ratio of balls, materials and solvent is 3:1:(0.4-1.0), and the grinding time is 2-4h;

[0040] The drying process is: vacuum drying at 70-80°C for 8-12 hours.

[0041] In the above technical solution, alumina and zirconia materials are mixed and sintered to form a composite ceramic. Alumina can exert compressive stress on the zirconia grains, so that the grain boundaries of the two have good bonding strength and cracks are not easy to form; it can inhibit the TM phase transformation and grain growth of zirconia and achieve grain refinement. Alumina can fill the pores in the material and promote densification sintering; and through the difference in thermal expansion coefficient between it and zirconia, it eliminates the residual stress generated by high-temperature cooling, so that the composite ceramic has better bending strength, fracture toughness and high temperature resistance.

[0042] The introduction of metallic titanium into the material system of ceramic materials can fill the gaps between materials such as zirconium oxide / aluminum oxide, aluminum oxide / modified silicon carbide, reduce defects between grains, and enhance grain boundary strength, thereby improving the mechanical properties of ceramic materials and achieving the effect of reinforcement and toughening. Under high temperature and low oxygen conditions, titanium melts to form a liquid phase, diffuses in the molybdenum disilicide of modified silicon carbide, combines with surface silicon atoms to form titanium-silicon compounds, and promotes the formation of molybdenum-silicon compounds with lower silicon content, such as Mo5Si3, Mo3Si2, and Mo3Si, which can promote sintering, expand the sintering temperature range, improve the toughness and ductility of molybdenum disilicide, and further improve the fracture toughness of the ceramic material produced.

[0043] In an air atmosphere, metal titanium is oxidized to form titanium oxide, which alleviates oxygen vacancy defects and can form titanium aluminum oxide (aluminum titanate) with a low thermal expansion coefficient with aluminum oxide, further improving the high-temperature oxidation resistance and thermal shock resistance of the prepared ceramic material. The above-mentioned titanium aluminum oxide can react with zirconium oxide to form a solid solution, effectively pin the grain boundaries, which is conducive to grain refinement, effectively improves the strength of aluminum titanate, and makes aluminum titanate have excellent stability and improves its high-temperature decomposition characteristics. The ceramic material system also contains yttrium oxide, which has good surface activity, can improve the wettability of the material, promote the formation of a low-melting-point liquid phase, allow the material to fill the pores, reduce the sintering temperature of aluminum titanate ceramics, and promote the densification of the aluminum titanate structure; the element yttrium can form an equivalent substitution solid solution with aluminum titanate, its stability is further improved, the movement of grain boundaries is hindered, and grain refinement is promoted; it can also promote the preferential growth of aluminum titanate crystals, so that the crystals are transformed from equiaxed crystals to columnar crystals, achieving the effect of self-toughening and strengthening, and improving its mechanical properties; it can also effectively reduce the thermal expansion coefficient of aluminum titanate, and combined with molybdenum disilicide, further slow down the generation of thermal stress inside the ceramic material, avoid the formation of cracks, and further improve the thermal shock resistance of the ceramic material.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The high temperature resistant zirconia ceramic material of the present invention uses zirconia as the matrix of the ceramic material, adds silicon carbide for toughening, and improves the high temperature mechanical properties of the ceramic material; adds rare earth oxide yttrium oxide and alkali metal oxide calcium oxide to improve the stability of the system, thereby obtaining a ceramic material with high heat resistance that can withstand high temperatures of 1800°C-1850°C.

[0046] 2. The high temperature resistant zirconia ceramic material of the present invention can effectively improve the high temperature oxidation resistance of the modified silicon carbide and the ceramic material produced by loading molybdenum disilicide with aluminum doping on silicon carbide on the basis of the above materials, and improve the mechanical properties and high temperature thermal shock resistance of the ceramic material produced. The addition of metal titanium and aluminum oxide can fill the gaps in the system, reduce defects between grains, enhance grain boundary strength, improve the mechanical properties of the ceramic material, and play a role in strengthening and toughening; and can promote the formation of molybdenum silicon compounds with lower silicon content, improve the toughness and ductility of molybdenum disilicide, and further improve the room temperature fracture toughness and thermal shock resistance of the ceramic material produced. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] In the following specific implementations,

[0049] Molybdenum disulfide: purity 99.9%, particle size 10μm, sourced from Bohuasi Nanotechnology Co., Ltd.

[0050] Silicon: purity 99.5%, particle size 45μm, sourced from Beijing Dadi Zelin Silicon Industry Co., Ltd.

[0051] Aluminum: purity 99.5%, particle size 3-5μm, sourced from Angang Industrial Fine Aluminum Powder Co., Ltd.;

[0052] Activated carbon: purity 99%, particle size 50 mesh, sourced from Sinopharm Chemical Reagent Co., Ltd.;

[0053] Titanium: purity 99.5%, particle size 0.5-1 μm, sourced from Fulanshi (Beijing) Nanotechnology Co., Ltd.;

[0054] Alumina: purity 99.0%, particle size 0.5-1 μm, sourced from Aluminum Corporation of China;

[0055] Zirconia: particle size 100-500nm, sourced from Jiaozuo Lifeng Industrial Co., Ltd.

[0056] Yttrium oxide: 5μm, from Jiangyin Jiahua New Materials Resources Co., Ltd.;

[0057] Calcium oxide: from Chengdu Kelong Chemical Reagent Factory;

[0058] Silicon carbide: 45μm, sourced from Huayu Abrasives Factory in Zhengzhou High-tech Industrial Development Zone.

[0059] Embodiment 1: A processing technology for high temperature resistant zirconia ceramic material, comprising the following process steps:

[0060] Step 1: Preparation of modified silicon carbide:

[0061] Molybdenum disulfide, silicon, aluminum and activated carbon are mixed, and anhydrous ethanol is added for grinding. Zirconia balls are used for grinding. The mass ratio of balls, materials and solvent is 3:1:0.4. The ball mill speed is 250r / min and the grinding time is 4h. The mixture is vacuum dried at 70°C for 12h and passed through a 300-mesh sieve. The mixture is pre-pressed at a pressure of 190MPa for 8min. In an argon atmosphere, the gas flow rate is 400mL / min, the temperature is increased to 630°C at a heating rate of 20°C / min, the temperature is increased to 1500°C at a heating rate of 5°C / min, and the mixture is sintered for 150min at a temperature preservation temperature. The mixture is cooled to room temperature and crushed to less than 10μm to obtain modified silicon carbide.

[0062] The molar ratio of molybdenum disulfide, silicon, aluminum and carbon is 1:4.25:0.04:0.25;

[0063] Step 2: Preparation of ceramic materials:

[0064] Titanium, modified silicon carbide, aluminum oxide, zirconium oxide, yttrium oxide and calcium oxide were mixed, and anhydrous ethanol was added for grinding. Zirconium oxide balls were used for grinding. The mass ratio of balls, materials and solvent was 3:1:1. The ball mill speed was 250r / min and the grinding time was 4h. The mixture was vacuum dried at 70°C for 12h and ground through a 170-mesh sieve. The mixture was pre-pressed. The process conditions of the pre-pressing treatment were: cold isostatic pressing, pressure of 150MPa, and time of 200s.

[0065] Hot pressing sintering, the process is: in argon atmosphere, the sintering temperature is 1690℃, the sintering pressure is 30MPa, and the sintering time is 20min; in air atmosphere, the temperature is lowered to 1450℃, and the temperature and pressure are kept to sinter for 8h; the furnace is cooled to room temperature, and the ceramic material is obtained by grinding and polishing;

[0066] The ceramic material includes the following components by mass: 94.5 parts of zirconium oxide, 3 parts of modified silicon carbide, 2 parts of titanium, 4.2 parts of aluminum oxide, 2.0 parts of yttrium oxide and 0.5 parts of calcium oxide.

[0067] Embodiment 2: A processing technology for high temperature resistant zirconia ceramic material, comprising the following process steps:

[0068] Step 1: Preparation of modified silicon carbide:

[0069] Molybdenum disulfide, silicon, aluminum and activated carbon are mixed, and anhydrous ethanol is added for grinding. Zirconia balls are used for grinding. The mass ratio of balls, materials and solvent is 3:1:0.7. The ball mill speed is 360r / min and the grinding time is 3h. The mixture is vacuum dried at 75°C for 10h and passed through a 325-mesh sieve. The mixture is pre-pressed at a pressure of 195MPa for 6min. The mixture is heated to 665°C at a heating rate of 15°C / min and to 1525°C at a heating rate of 5°C / min in an argon atmosphere at a gas flow rate of 400mL / min. The mixture is then heated to 1525°C at a heating rate of 5°C / min and sintered for 120min. The mixture is cooled to room temperature and crushed to less than 10μm to obtain modified silicon carbide.

[0070] The molar ratio of molybdenum disulfide, silicon, aluminum and carbon is 1:5.25:0.05:1.0;

[0071] Step 2: Preparation of ceramic materials:

[0072] Titanium, modified silicon carbide, aluminum oxide, zirconium oxide, yttrium oxide and calcium oxide were mixed, and anhydrous ethanol was added for grinding. Zirconium oxide balls were used for grinding. The mass ratio of balls, materials and solvent was 3:1:0.6. The ball mill speed was 360r / min and the grinding time was 3h. The mixture was vacuum dried at 75°C for 10h and ground through a 200-mesh sieve. The mixture was pre-pressed. The process conditions of the pre-pressing treatment were: cold isostatic pressing, pressure of 175MPa, and time of 160s.

[0073] Hot pressing sintering, the process is: in argon atmosphere, sintering temperature is 1700℃, sintering pressure is 35MPa, and sintering time is 15min; in air atmosphere, cooling to 1500℃, keeping heat and pressure and sintering for 7h; cooling to room temperature with the furnace, grinding and polishing to obtain ceramic material;

[0074] The ceramic material comprises the following components by mass: 91.1 parts zirconium oxide, 4.5 parts modified silicon carbide, 4 parts titanium, 8.5 parts aluminum oxide, 3.6 parts yttrium oxide and 0.8 parts calcium oxide.

[0075] Embodiment 3: A processing technology for high temperature resistant zirconia ceramic material, comprising the following process steps:

[0076] Step 1: Preparation of modified silicon carbide:

[0077] Molybdenum disulfide, silicon, aluminum and activated carbon are mixed, and anhydrous ethanol is added for grinding. Zirconia balls are used for grinding. The mass ratio of balls, materials and solvent is 3:1:0.4. The ball mill speed is 480r / min and the grinding time is 2h. The mixture is vacuum dried at 80°C for 8h and passed through a 400-mesh sieve. The mixture is pre-pressed at a pressure of 200MPa for 5min. The mixture is heated to 700°C at a heating rate of 10°C / min and then to 1550°C at a heating rate of 5°C / min in an argon atmosphere. The mixture is sintered at this temperature for 100min. The mixture is cooled to room temperature and crushed to less than 10μm to obtain modified silicon carbide.

[0078] The molar ratio of molybdenum disulfide, silicon, aluminum and carbon is 1:6:0.06:2;

[0079] Step 2: Preparation of ceramic materials:

[0080] Titanium, modified silicon carbide, aluminum oxide, zirconium oxide, yttrium oxide and calcium oxide were mixed, and anhydrous ethanol was added for grinding. Zirconium oxide balls were used for grinding. The mass ratio of balls, materials and solvent was 3:1:0.4. The ball mill speed was 480r / min and the grinding time was 2h. The mixture was vacuum dried at 80°C for 8h and ground through a 250-mesh sieve. The mixture was pre-pressed. The process conditions of the pre-pressing treatment were: cold isostatic pressing, pressure of 200MPa, and time of 120s.

[0081] Hot pressing sintering, the process is: in argon atmosphere, sintering temperature is 1720℃, sintering pressure is 30MPa, and sintering time is 10min; in air atmosphere, cooling to 1550℃, keeping heat and pressure and sintering for 6h; cooling to room temperature with the furnace, grinding and polishing to obtain ceramic material;

[0082] The ceramic material includes the following components by mass: 87.7 parts zirconium oxide, 6 parts modified silicon carbide, 6 parts titanium, 12.7 parts aluminum oxide, 5.3 parts yttrium oxide and 1.0 part calcium oxide.

[0083] Embodiment 4: A processing technology for high temperature resistant zirconia ceramic material, comprising the following process steps:

[0084] Zirconium oxide, yttrium oxide, silicon carbide and calcium oxide are mixed, and anhydrous ethanol is added for grinding. Zirconium oxide balls are used for grinding. The mass ratio of balls, materials and solvent is 3:1:1. The ball mill speed is 250r / min and the grinding time is 4h. The mixture is vacuum dried at 70°C for 12h and ground through a 170-mesh sieve. The mixture is pre-pressed and the process conditions of the pre-pressing treatment are: cold isostatic pressing, pressure of 150MPa and time of 200s. The mixture is hot-pressed and sintered in an argon atmosphere at a sintering temperature of 1250-1350°C, a heat preservation time of 2h and a sintering pressure of 30MPa. The mixture is cooled to room temperature with the furnace, and then ground and polished to obtain a ceramic material.

[0085] The ceramic material comprises the following components by mass: 94.5 parts zirconium oxide, 3 parts silicon carbide, 2 parts yttrium oxide and 0.5 parts calcium oxide.

[0086] Comparative Example 1: A processing technology for a high temperature resistant zirconia ceramic material, comprising the following process steps:

[0087] Titanium, silicon carbide, aluminum oxide, zirconium oxide, yttrium oxide and calcium oxide were mixed, and anhydrous ethanol was added for grinding. Zirconium oxide balls were used for grinding. The mass ratio of balls, materials and solvent was 3:1:1. The ball mill speed was 250r / min and the grinding time was 4h. The mixture was vacuum dried at 70°C for 12h and ground through a 170-mesh sieve. The mixture was pre-pressed. The process conditions of the pre-pressing treatment were: cold isostatic pressing, pressure of 150MPa, and time of 200s.

[0088] Hot pressing sintering, the process is: in argon atmosphere, the sintering temperature is 1690℃, the sintering pressure is 30MPa, and the sintering time is 20min; in air atmosphere, the temperature is lowered to 1450℃, and the temperature and pressure are kept to sinter for 8h; the furnace is cooled to room temperature, and the ceramic material is obtained by grinding and polishing;

[0089] The ceramic material includes the following components by mass: 94.5 parts zirconium oxide, 3 parts silicon carbide, 2 parts titanium, 4.2 parts aluminum oxide, 2.0 parts yttrium oxide and 0.5 parts calcium oxide.

[0090] Comparative Example 2: A processing technology for high temperature resistant zirconia ceramic material, comprising the following process steps:

[0091] Titanium, silicon carbide, zirconium oxide, yttrium oxide and calcium oxide were mixed, and anhydrous ethanol was added for grinding. Zirconium oxide balls were used for grinding. The mass ratio of balls, materials and solvent was 3:1:1. The ball mill speed was 250r / min and the grinding time was 4h. The mixture was vacuum dried at 70°C for 12h and ground through a 170-mesh sieve. The mixture was pre-pressed. The process conditions of the pre-pressing treatment were: cold isostatic pressing, pressure of 150MPa, and time of 200s.

[0092] Hot pressing sintering, the process is: in argon atmosphere, the sintering temperature is 1690℃, the sintering pressure is 30MPa, and the sintering time is 20min; in air atmosphere, the temperature is lowered to 1450℃, and the temperature and pressure are kept to sinter for 8h; the furnace is cooled to room temperature, and the ceramic material is obtained by grinding and polishing;

[0093] The ceramic material includes the following components by mass: 94.5 parts zirconium oxide, 3 parts silicon carbide, 2 parts titanium, 2.0 parts yttrium oxide and 0.5 parts calcium oxide.

[0094] Comparative Example 3: A processing technology for high temperature resistant zirconia ceramic material, comprising the following process steps:

[0095] Silicon carbide, zirconium oxide, yttrium oxide and calcium oxide were mixed, and anhydrous ethanol was added for grinding. Zirconium oxide balls were used for grinding. The mass ratio of balls, materials and solvent was 3:1:1. The ball mill speed was 250r / min and the grinding time was 4h. The mixture was vacuum dried at 70°C for 12h and ground through a 170-mesh sieve. The mixture was pre-pressed. The process conditions of the pre-pressing treatment were: cold isostatic pressing, pressure of 150MPa, and time of 200s.

[0096] Hot pressing sintering, the process is: in argon atmosphere, the sintering temperature is 1690℃, the sintering pressure is 30MPa, and the sintering time is 20min; in air atmosphere, the temperature is lowered to 1450℃, and the temperature and pressure are kept to sinter for 8h; the furnace is cooled to room temperature, and the ceramic material is obtained by grinding and polishing;

[0097] The ceramic material includes the following components by mass: 94.5 parts zirconium oxide, 3 parts silicon carbide, 2.0 parts yttrium oxide and 0.5 parts calcium oxide.

[0098] Experiment: Take the ceramic materials obtained in Examples 1-4 and Comparative Examples 1-3, prepare samples, test their properties respectively and record the test results:

[0099] Normal temperature performance test:

[0100] Bending strength test: The test was conducted using an electronic universal testing machine with a three-point bending strength method. The test temperature was 25°C, the span was 30mm, the speed of the indenter downward movement was 0.5mm / min, and the sample size was 40mm×5mm×5mm.

[0101] Fracture toughness test: Vickers hardness tester, indentation method, test temperature 25℃, load 10kgf, hold for 15s;

[0102] High temperature performance test:

[0103] Thermal shock resistance test: The thermal shock resistance of the sample was tested using a temperature-controlled resistance furnace. The conditions for one thermal shock cycle were: 25-1100°C, 10 minutes of heat preservation, and air cooling to room temperature. After 30 thermal shock cycles, the bending strength of the sample was tested again, and its strength loss rate was calculated as a characterization of the thermal shock resistance of the sample.

[0104] High-temperature antioxidant performance test: Use a temperature-controlled resistance furnace to place the sample in an air atmosphere, heat it to 1300°C at a heating rate of 10°C / min, keep it warm for 1h, cool it to room temperature with the furnace, repeat 5 times, test the bending strength of the sample again, and calculate its strength loss rate as a characterization of the high-temperature antioxidant performance of the sample.

[0105] Flexural strength(MPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Thermal shock strength loss (%) Oxidation strength loss (%) Example 1 882.1 6.7 -1.0 -2.3 Example 2 860.7 7.1 -1.5 -4.0 Example 3 847.5 7.8 -2.2 -3.1 Example 4 834.6 4.9 16.4 14.0 Comparative Example 1 862.2 6.3 2.3 5.2 Comparative Example 2 874.7 5.8 9.1 8.6 Comparative Example 3 816.0 5.6 13.7 11.3

[0106] According to the data in the above table, we can clearly draw the following conclusions:

[0107] The ceramic materials obtained in Examples 1-4 are compared with the ceramic materials obtained in Comparative Examples 1-3. The test results show that:

[0108] Compared with Example 4 and the comparative example, the ceramic materials obtained in Examples 1-3 have higher flexural strength and fracture toughness data and lower thermal shock strength loss and oxidation strength loss; among them, the strength loss of the ceramic materials obtained in Examples 1-3 after thermal shock and oxidation is negative, that is, the flexural strength increases, and the reason may be that: high temperature and oxidation promote the crystal transformation and increase of titanium oxide in the system, and the amount of aluminum titanate increases, which is conducive to the gradient formation of aluminum titanate / aluminum oxide composite ceramics; and the compressive stress and solid solution diffusion at the grain interface hinder the generation and expansion of internal cracks (caused by zirconium oxide phase transformation, anisotropy of aluminum titanate, etc.), and self-healing occurs, thereby improving the flexural strength after thermal shock; this fully demonstrates that the present invention achieves the improvement of the mechanical properties and high temperature properties of the prepared ceramic material.

[0109] Compared with Example 1, the silicon carbide in Example 1 has not been modified; compared with Example 1, the component aluminum oxide is not added in Example 2; the components aluminum oxide and metal titanium are not added in Example 3; compared with Example 3, the sintering process in Example 4 is different; from the above, it can be seen that the bending strength and fracture toughness data of the ceramic materials obtained in Example 4 and Examples 1-3 are relatively low, and the reasons may be: the poor interface bonding ability between materials and the lack of tough materials; and the thermal shock strength loss and oxidation strength loss are relatively high, and the reasons may be: the thermal shock and oxidation experiments cause the t-ZrO2 in the ceramic material structure to change, and the phase change process is accompanied by volume changes, resulting in the generation and expansion of cracks. Due to the lack of interaction at the grain boundary, the cracks expand and increase; and the oxidizing environment oxidizes the silicon carbide in the system, and the SiO2 phase in the system increases, thereby causing the mechanical properties to decrease and the high-temperature performance to deteriorate. In summary, the setting of the ceramic material components and their processes in this application can promote the improvement of the mechanical properties and high-temperature properties of the prepared ceramic materials.

[0110] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0111] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A processing technology for high temperature resistant zirconia ceramic material, characterized by: The process steps include: Mix titanium, modified silicon carbide, aluminum oxide, zirconium oxide, yttrium oxide and calcium oxide, add anhydrous ethanol to grind, dry, grind through a 170-250 mesh sieve; pre-press treatment A; hot press sintering A, and cool to obtain a ceramic material; The modified silicon carbide is prepared by the following process: Molybdenum disulfide, silicon, aluminum and activated carbon are mixed, anhydrous ethanol is added to grind, dried, and passed through a 300-400 mesh sieve; pre-pressing treatment B, sintering B, and cooling to obtain modified silicon carbide; In the preparation process of ceramic materials, the process conditions of hot pressing sintering A are: in an argon atmosphere, the sintering temperature is 1690-1720°C, the sintering pressure is 30-40MPa, and the sintering time is 10-20min; in an air atmosphere, the temperature is lowered to 1450-1550°C, and the temperature and pressure are kept for 6-8h; In the preparation process of modified silicon carbide, the process conditions of sintering B are: under argon atmosphere, gas flow rate 400mL / min, heating to 630-700℃ at a heating rate of 10-20℃ / min, heating to 1500-1550℃ at a heating rate of 5℃ / min, and sintering at a temperature of 100-150min.

2. The processing technology of a high temperature resistant zirconia ceramic material according to claim 1 is characterized in that: In the preparation process of modified silicon carbide, the process conditions of the pre-pressing treatment B are: the pre-pressing treatment is continued at a pressure of 190 to 200 MPa for 5 to 8 minutes.

3. The processing technology of a high temperature resistant zirconia ceramic material according to claim 1 is characterized in that: The molar ratio of molybdenum disulfide, silicon, aluminum and carbon is 1:(4.25-6.0):(0.04-0.06):(0.25-2.0).

4. The processing technology of a high temperature resistant zirconia ceramic material according to claim 1 is characterized in that: In the preparation process of the ceramic material, the process conditions of the pre-pressing treatment A are: cold isostatic pressing, pressure 150-200 MPa, time 120-200 s.

5. The processing technology of a high temperature resistant zirconia ceramic material according to claim 1 is characterized in that: The ceramic material comprises the following components by mass: 87.7 to 94.5 parts of zirconium oxide, 3 to 6 parts of modified silicon carbide, 2 to 6 parts of titanium, 4.2 to 12.7 parts of aluminum oxide, 2.0 to 5.3 parts of yttrium oxide and 0.5 to 1.0 parts of calcium oxide.

6. A high temperature resistant zirconia ceramic material obtained by the processing technology according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Nano ceramic cutter and preparation method thereof

    CN103708832A

  • Method for preparing Mo(Si, Al)2-SiC metal ceramic composite material by reactive melt infiltration process

    CN104451319A

  • Method of preparing Mo(Si,Al)-2-SiC metal ceramic composite material through reaction method

    CN104451320A

  • Zirconium-oxide-based nanocomposite ceramic die material and preparation method thereof

    CN107602117A

  • Zirconia sink roll shaft sleeve ceramic and preparation method thereof

    CN111018522A